(untitled) (Applied Biological Research, 2012)
Arginyl-arginyl-4-methoxy-β-naphthylamide (Arg-Arg-4mβNA) hydro lyzeing activity is known as dipeptidylpeptidase-III (DPP-III). DPP-III enzyme hydrolyzes various bioactive peptides, including enkephalins, angiotensins, gastric peptides and Arg-Arg-4mβNA. We report the presence of DPP-III enzyme in plants for the first time. The enzyme was noticed in mung bean [Vigna radiata] seeds germinated at 25ºC for 48 h. The crude enzyme preparation had optimum activity at alkaline pH of 8.0. Sub-cellular distribution of this enzyme revealed its cytosolic localization. Enzyme activity when investigated in different parts of mung bean plant revealed maximum activity in seeds followed by roots, stem and leaves. The ubiquitous distribution of this enzyme signifies house keeping role of this enzyme in plant physiology. Maximum activity in seeds indicates its possible role in germination.